The Representation of Sadness in the Qur'an: A Semiotic Analysis of Prophetic Narratives - Agil Husein Al Munawar; Mohamad Zaka Al Farisi (Asalibuna, 2026)
This study examines the representation of sadness in the Qur'anic stories of the prophets using Roland Barthes' semiotic framework integrated with Nasr Hamid Abu Zayd's hermeneutics and Pargament's Positive Religious Coping theory. Employing a qualitative content analysis design, the study analyzes four prophetic narratives selected through purposive sampling based on themes of family relationships and experiences of suffering. The findings reveal that the Qur'an constructs sadness through three interconnected levels of signification. At the denotative level, different lexical signifiers represent distinct forms and intensities of sadness. At the connotative level, sadness is transformed into a spiritual process oriented toward patience, surrender, and trust in Allah. At the mythological level, the Qur'an constructs a counter-myth that redefines emotional responses to suffering. Rather than legitimizing the pre-Islamic tradition of hysterical mourning, the narrative of Prophet Ya'qub naturalizes somatic sadness as a legitimate human condition without diminishing faith, while the story of Prophet Nūḥ reconstructs the concept of family by prioritizing the bond of faith over biological lineage. Furthermore, the prophetic narratives embody four forms of Positive Religious Coping: Collaborative Religious Coping, Benevolent Religious Reappraisal, Religious Surrender, and Spiritual Connection. These findings contribute to Arabic language pedagogy by demonstrating how lexical-semantic and semiotic analyses of Qur'anic discourse can enrich the teaching of Qur'anic Arabic, semantics, and discourse interpretation while fostering students' emotional and spiritual literacy.   Abstrak Penelitian ini bertujuan menganalisis representasi kesedihan dalam kisah-kisah para nabi di dalam Al-Qur'an menggunakan kerangka semiotika Roland Barthes yang diintegrasikan dengan hermeneutika Nasr Hamid Abu Zayd dan teori Positive Religious Coping Kenneth Pargament. Penelitian ini menggunakan pendekatan analisis isi kualitatif terhadap empat narasi para nabi yang dipilih secara purposive berdasarkan tema hubungan keluarga dan pengalaman penderitaan. Hasil penelitian menunjukkan bahwa Al-Qur'an membangun representasi kesedihan melalui tiga tingkat pertandaan yang saling berhubungan. Pada tataran denotatif, Al-Qur'an menggunakan pilihan leksikal yang berbeda untuk merepresentasikan ragam bentuk dan intensitas kesedihan. Pada tataran konotatif, kesedihan ditransformasikan menjadi proses spiritual yang mengarahkan manusia kepada kesabaran, kepasrahan, dan kepercayaan kepada Allah. Pada tataran mitologis, Al-Qur'an membangun counter-myth yang merekonstruksi respons manusia terhadap penderitaan. Alih-alih melegitimasi tradisi meratap histeris pada masyarakat Arab pra-Islam, kisah Nabi Ya'qub menaturalisasikan kesedihan somatik sebagai bagian yang wajar dari fitrah manusia tanpa mengurangi kualitas keimanan, sedangkan kisah Nabi Nuh merekonstruksi konsep keluarga dengan menempatkan ikatan akidah di atas hubungan biologis. Selain itu, narasi para nabi merepresentasikan empat bentuk Positive Religious Coping, yaitu Collaborative Religious Coping, Benevolent Religious Reappraisal, Religious Surrender, dan Spiritual Connection. Temuan ini berkontribusi terhadap pedagogi bahasa Arab dengan menunjukkan bahwa analisis leksikal-semantik dan semiotik terhadap wacana Al-Qur'an dapat memperkaya pembelajaran bahasa Arab Al-Qur'an, semantik, dan interpretasi wacana, sekaligus mengembangkan literasi emosional dan spiritual peserta didik.